Competência em informação na UFPR TV: a inter-relaçâo entre informação, conhecimento e comunicação - Cavalcante, Luciane de Fátima Beckman [UNESP] (2014)
In the scenario of the Information Society, University television ( TVU ) is a mean of mass communication that incorporates principles of social structure changes , from the dissemination of culture, knowledge and education , which can favor the formation of attitudes and opinions , instilling critical thinking in individuals, promoting dialogue between society and the University through the dissemination of knowledge produced by academics . As an organization situated in the communication area , TVU is based on information and knowledge and depends on these factors for its maintenance and survival in this environment characterized by complexity, innovation demand and new forms of management, in particular what refers to access and information use in order to build knowledge and serving the academic community . According to this, the central hypothesis of the thesis has been established that information literacy , while link mainstreaming in decision making permeates the processes and activities and interacts with organizational outcomes . So, the central objective was defined as : to identify and analyze the information competence of organizational subjects of a University television and its inter - relationship with access and intelligent use of information and knowledge in order to contribute for building theoretical basis for those interested in developing actions and practices in this direction, and supported on mass communication. For the operationalization of objectives and verification of central research hypothesis , we opted for a case study of descriptive and exploratory nature in University television , at Federal University of Paraná ( UFPR TV ) , using methods as the following instruments to collect data: exploratory visit to the mentioned television and semi - structured interview . As a benchmark for analyzing the data collected we opted for the content method for analysis Laurence Bardin, more specifically, Categorical...